(untitled) (Research, Society and Development, 2021)
Homegarden agroforestry is strategic alternatives, guaranteeing family income, food security, and the possibility of increasing diversity, stability, and sustainability of the productive system. However, in order to design and implement these systems, it is important to take into account regional natural diversity and to understand the ecological dynamics of its plant populations. The present study carried out in southern Brazil aimed to survey floristic data and characterizes three existing orchards (Q1, Q2 e Q3), to design and subsequently implement an agroforestry homegarden model for the Pampa Biome. A survey of floristic and dendrometric data of the different existing plant strata was carried out. For the arboreous strata, we measured tree height and diameter at soil height, and for the shrub and herbaceous strata, we collected data on richness and abundance from the local biodiversity. Frequency, density, and diversity analyses were performed using the Shannon and Pielou equitability indexes. A workshop was organized with the farmers aiming the design an agroforestry homegarden model for the Pampa Biome. The analyzed plots showed similar conditions of soil, relief, and climate, although between them, there were differences in spacing and management practices. With regards to the management, Q1 proved to be abandoned, whereas Q2 and Q3 showed signs of ongoing management. In the Shannon and Pielou Equitability indices, Q2 had the highest numbers, and Q1, the lowest values. As for frequency and density, the Sida genus stood out within all plots. During the participatory design of the new agroforestry homegardens, native species were chosen mainly to produce fruits for self-consumption.